Demographical and Clinical Characteristics, Risk Factors, and Prognosis of Adult Patients with Herpes Zoster in Türkiye: A Retrospective, Multi-Center Study (VARICOMP-Adult Study) - Esin Senol; Alpay Azap; Selda Sayin Kutlu; Murat Kutlu; Ayse Erbay; Pelin Kocyigit; Emine Colgecen; Ozlem Ozbagcivan; Nilsel Ilter; Funda Yetkin; Serpil Sener; Birsen Mutlu; et al. (Infectious Disease Reports, 2025)
Introduction: Over the past few decades, the rising incidence of herpes zoster (HZ) rates appears to have been a global phenomenon. In Türkiye, there is a lack of comprehensive studies addressing the HZ burden of disease, risk factors, and clinical characteristics. The aim of the VARICOMP-Adult study was to evaluate the clinical and demographic findings of adult patients with HZ. Patients and Methods: We enrolled the medical records of 1955 patients, 1010 females and 945 males, aged between 18 and 97 years between 2009 and 2014. Results: The presence of underlying conditions was present in 35.5% of patients and 345 patients (17.6%) had immunosuppression; 18.0% of patients required hospitalization. The mean age, the presence of underlying conditions, and immunosuppression in hospitalized cases with HZ were higher than those in outpatients. Logistic regression analysis revealed the following risk factors for hospitalization: age, immunosuppression, hypertension, hematological disorders, transplantation, COPD, and the presence of HZ opthalmicus or disseminated disease. We observed seven HZ cases with mortality aged between 58 and 80 years, and all cases had an underlying condition; 9.9% of the entire population reported postherpetic neuralgia (PHN), and age and no previous antiviral medications were the risk factors for PHN. Conclusions: This is the largest nationwide study of adult patients with HZ. Effective healthcare interventions such as antiviral therapy and immunization could prove beneficial in combating disease and treating HZ complications, especially in the high-risk population and individuals of older ages.